A COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFICACY OF JANUBASTI FOLLOWED BY PATRAPINDA SWEDA AND JANUBASTI FOLLOWED BY ATASI UPANAHA SWEDA IN JANU SANDHIGATA VATA W.S.R TO OSTEOARTHRITIS OF KNEE JOINT - Ramesh, *Asha Mysore; Swamy, Vishal K; Goud, Kiran M (International Journal of Ayurveda and Pharma Research, 2019)
Janu Sandhigata Vata is a common Vata predominant disorder mainly caused in Vriddhavastha. It is a degenerative articular disorder caused in geriatric age group and its correlates with Osteoarthritis of knee joint. Being commonest form of articular disorders, Osteoarthritis poses a huge hindrance in day to day activities of the sufferer like walking, dressing and bathing etc. Due to Vriddaavasta, Uttarothara Dhatuposhana gets reduced and finally makes the person lame. Hence this study was conducted on 10 patients for 7 days to evaluate the efficacy of Janubasti with Moorchita Tila Taila followed by Patrapinda Sweda in Group A and Janubasti with Moorchita Tila Taila followed by Atasi Upanaha Sweda in Group B. The study reports significant relief in subjective parameters like Vatapurna Dritisparsha (joint crepitations), Sandhi Shoola (joint pain) and Prasarana akunchana pravriti sa vedana (pain during flexion and extension of joint) Sandhi Shotha (joint swelling) is completely relieved after the study. Assessment of results was done on the subjective parameters which showed highly significant changes in Vatapurna Drithisparsha, Sandhi Shotha and Prasarana Akunchana Vedana, and significant improvement in Sandhi Shoola in Group A. In group B Vatapurna Drithisparsha, Sandhi Shotha and Sandhi Shoola showed highly significant changes and Prasarana Akunchana Vedana showed significant changes.